Performance of a composite flow moulded carbon fibre reinforced osteosynthesis plate - Rohner, B.; Wieling, R.; Magerl, F.; Schneider, E.; Steiner, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Non-metallic implants have the advantage over metallic implants of reduction in artefact with CT and MR diagnostic imaging. In-vivo performance of a carbon fibre reinforced polyetheretherketone radiolucent plate (Snake Plate [SP]) with high stiffness, and fixed angle converging screws was compared with a seven-hole titanium Locking Compression Plate (LCP), using a sheep tibial osteotomy model (gap 0.6 mm). The sheep were divided into two groups, and the osteotomies were stabilized with a SP (n=6) or a LCP (n=6). The callus dimensions were measured radiographically at zero, two, four, six and eight weeks. The animals were euthanatized after eight weeks. Osteotomised and contralateral tibiae were tested in pairs torsion, to determine strength and stiffness. In the radii of six separate sheep, initial vascular disturbance after plate implantation was evaluated. All of the sheep of the SP and LCP groups showed maximal callus areas at six weeks. The differences between the groups, in callus dimension, were not significant at any time point. The median values for relative reduction (100 x [operated – contralateral] / contralateral) in strength of osteotomized tibiae was ™13.93% for the SP group and ™7.49% for the LCP group (p = 0.5228), and for stiffness it was ™24.44 % for the SP group and ™27.08% for the LCP group (p = 0.6481). Neither the SP nor LCP caused any notable disturbance in periosteal circulation. The SP appears to represent a valuable alternative to metallic implants for shaft fracture repair. The main advantages of the SP are radiolucency, high deformation resistance, internal fixator concept and converging screw configuration for optimal loading conditions in the bone-implant construct.
Keywords: Osteosynthesis; Locking Compression Plate; snake plate; carbon fibre reinforced polyetheretherketone; composite flow moulding